Perlindungan Hukum Terhadap Hak Khusus Pekerja Perempuan (Perbandingan UU Cipta Kerja dan UU Ketenagakerjaan) - Monicha Widyasputri; Bagus Sarnawa (Media of Law and Sharia, 2024)
Legal protection serves for the benefit, safety and guarantee of the rights obtained by workers. The legal protection of workers is regulated in the Manpower Law, in 2020 the Job Creation Law was passed, but caused several conflicts and confusing information regarding the reduction of protection of special rights of women workers, related to maternity leave, breastfeeding permits, and guarantees of protection in the work environment, because it was considered that there were several matters related to women's special rights that were changed or deleted from the previous Law. This law is considered more prosperous for employers than workers. The purpose of this study is to determine the comparison of legal protection for women's workers' leave rights in Indonesia according to the Manpower Law with the Job Creation Law and sanctions for violations of women's workers' rights. This research uses normative research methods, by examining library materials, documents and literature. This study analyzes and examines laws related to legal protection for women workers. The type of data used is secondary data. This study identifies special rights for women workers contained in the Manpower Law and the Job Creation Law. The results of this study show that the Job Creation Law does not change or remove special rights for women workers stipulated in the previous law. Therefore, this Job Creation Law has provided worker protection for women because it does not change the existing arrangements in the Manpower Law. This research hopefully makes material to straighten out related to confusion related to scattered issues related to women's special rights regulations contained in the Job Creation Law